2012
DOI: 10.4304/jltr.3.5.1015-1026
|View full text |Cite
|
Sign up to set email alerts
|

Depth and Breadth of Vocabulary Knowledge: Which Really Matters in Reading Comprehension of Iranian EFL Learners?

Abstract: Abstract-The present study tried to assess the roles of vocabulary knowledge in reading comprehension of Iranian EFL learners. Using the multivariate analysis, this study examined the roles of depth and breadth of vocabulary knowledge in reading comprehension of a group of Iranian EFL University students with a minimum vocabulary size of 3,000 word families as was measured by Schmitt's (2001) Vocabulary Levels Test. The study found that 1) the test scores on vocabulary breadth, vocabulary depth and reading com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 39 publications
4
16
2
Order By: Relevance
“…The results are also in line with a host of other studies on the role of breadth and depth dimensions of vocabulary in reading comprehension (e.g., Moinzadeh & Moslehpour, 2012;Qian, 1999;Rashidi & Khosravi, 2010). Additionally, lexical inferencing success which is an important process in receptive skills of listening and reading (Parel, 2004), was found to be closely associated with performance on these two aspects of vocabulary knowledge (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…The results are also in line with a host of other studies on the role of breadth and depth dimensions of vocabulary in reading comprehension (e.g., Moinzadeh & Moslehpour, 2012;Qian, 1999;Rashidi & Khosravi, 2010). Additionally, lexical inferencing success which is an important process in receptive skills of listening and reading (Parel, 2004), was found to be closely associated with performance on these two aspects of vocabulary knowledge (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…The question of depth and breadth of vocabulary is also important. Evidence suggests that breadth of vocabulary is more important than depth of vocabulary in the reading comprehension process (Moinzadeh & Moslehpour, 2012). Although, a similar study by Kang et al (2012) reported contrasting results.…”
Section: Introductionmentioning
confidence: 94%
“…Breadth of vocabulary refers to “the number of words whose meaning has at least some superficial knowledge” ( Qian, 2002 ). Many studies have shown a positive relationship between receptive vocabulary knowledge and reading comprehension ( Qian, 1999 , 2002 ; Farvardin and Koosha, 2011 ; Moinzadeh and Moslehpour, 2012 ; Yunus et al, 2016 ). Moreover, a large size of receptive vocabulary may help learners to retain more words in the long-term ( Webb, 2007 ).…”
Section: Literature Reviewmentioning
confidence: 99%